The Place of S Genotype of Mycobacterium Tuberculosis Which is Endemic to the Republic of Sakha (Yakutia), in the Global Phylogeny according to Results of Whole-Genome Sequencing - V. V. Sinkov; G. I. Alekseeva; S. N. Zhdanova; M. K. Vinokurova; E. S. Prokopiev; O. B. Ogarkov (Туберкулез и болезни лёгких)
The objective: to assess the stability of circulation of S genotype and S-like strains of M. tuberculosis (MTB) in the Republic of Sakha (Yakutia) over a 12-year period and perform their phylogenetic identification relative to the L4.4 Euro-American subline.Subjects and Methods. Between 2009 and 2022, 513 MTB strains isolated from pulmonary tuberculosis patients were studied using molecular genetic methods. 92 isolates belonging to S genotype or having an S-like genetic profile were found. Whole-genome sequencing of five strains of S genotype that circulated in the territory of the Republic of Sakha (Yakutia) in 2020-2022 was carried out. A global phylogenetic analysis was performed and evolutionary relationship of the obtained genomes was determined, a RT-PCR test was developed for the rapid detection of S genotype strains.Results. In the territory of the Republic of Sakha (Yakutia), there is a stable circulation of S and S-like MTB genotypes belonging to the L4.4 Euro-American subline, the L4.4.1.1 subtype. The evolutionary model has confirmed the previously stated hypothesis that the spread of the S genotype among the indigenous population of Yakutia is associated with mass exposure to the Russian settlers which started from the beginning of the 17th century.Conclusion. Spread of MTB strains of the L4.4 Euro-American subline, L4.4.1.1 subtype, among the indigenous populations of New Zealand, Canada and Yakutia in the 17th-19th centuries is very similar.